การเพิ่มประสิทธิภาพในกระบวนการบรรจุของโรงงานผลิตขนมขบเคี้ยว - วุฒิชัย วิชัยขัทคะ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
The purpose of this independent study was to increase efficiency in packing process of one snack factory. The objectives of this work were to reduce and set up the number of workers in the packing process. The concept of work study was used to analyze the existing production line through flow diagram and process chart. Improvement solutions were proposed based on 5W1H and ECRS concept. The results from the improvement solutions were affected on reducing unnecessary operations, combining, rearranging and simplifying working steps and balancing work flow as a final result. Then, existing and improving systems were compared to evaluate the improvement solutions for real implementing in this company. The results of the improved system showed that, the manufacturing cycle time was reduced from 4.22 minutes to 3.96 minutes that was 6.16% reduction, the number of operations was reduced from 8 to 7 steps that was 12.50% reduction and the number of workers was reduced from 39 workers to 30 workers that was 23.08% reduction in labor cost.